Mechanical Properties Determination Of Mild Steel And Stainless Steel Joint Fabricated By MIG Welding Process - Shahrir, Sahari (UTeM, 2010)
The purpose of this study is to determine the mechanical properties and the microstructure behavior at weldment and HAZ of mild steel and stainless steel joint fabricated using MIG welding process. Material from grade Austenitic stainless steel(AISI 304) and mild steel (AISI 1010) with both thickness 4 mm were used. Welding design was done in single groove butt joint and weld using 1.2 mm and 0.8 mm diameter size of filler wire (ER309). Welding machine (WIM 210S) was used with selected parameter with involved voltage, wire feed speed and gas flow rate. Mechanical properties were evaluated in tensile tests, Charpy-V toughness tests, and hardness test. In addition microstructure examinations were carried out. Base on the finding, there was changes in hardness value on base metal, weldment and HAZ area. High hardness value has been identified at both HAZ area of dissimilar weld. Tensile test show at 1.2 mm strength was weaker than 0.8 mm joint. All specimens were fracture at HAZ near AISI 1010 side because of lack of fusion. At their barrier microstructures reveal that present of crack at HAZ near AISI 1010 and show little dilution in intermetallic of dissimilar metal. No ferrite structure present because MIG welding provide rapid cooling. All the implication in the dissimilar weld disturbance and affect the whole properties.